Peran Notaris Dalam Meningkatkan Pengetahuan Hukum Pekerja Seni - Meldawati Majid; lrwan Santosa (Jurnal Nuansa Kenotariatan, 2015)
This research aim to realize the deal of the parties concerned, the laws and regulations in force in Indonesia (positive law) to facilitate both theoretical and/or practices. Specialized in this research are find artist in making agreements/contracts have not been in the form of notarial deed (deed authentic). The situation occurs according to internal factors artists include: lack of knowledge about the making of the agreement/ contract, lack of knowledge in the profession of notary authority and position, not a relationship that is conducive to the notary.This research is a normative law (doctrinal)  based on secondary data. The research approach used to analyze the problems in this research include: (a) Con- ceptual approaches; (b) statute  approach; and (c) a conceptual approach. Therefore, this result is expected to improve the legal knowledge among artists in person and/or organization, to support the development of In- donesian art world becomes more advances and has a strong competitive edge for artists to make any agreement/contracts with related parties based on a better knowledge of the law.Keywords: Knowledge of the law, deed authentic, notary, artists